The periaqueductal grey area and control of blood pressure in neurodegeneration - Sitsapesan, H; Green, A; Aziz, T; Pereira, E (2013)
The periaqueductal/periventricular grey area (PAG/PVG) is a midbrain nucleus with an important role in pain signalling and autonomic control. We present the case of an initially hypertensive man who developed a presumed neurodegenerative disorder over a decade, characterised by progressive right-sided chronic pain, extra-pyramidal symptoms and autonomic dysfunction including postural hypotension, sleep apnoea, and bladder instability. He underwent a variety of treatments for his symptoms, including deep brain stimulation (DBS) of the PAG/PVG. 24-h blood pressure monitoring was carried out 1 and 5 years after implantation. Although the DBS initially produced a significant reduction in blood pressure, the effect was significantly reversed when the same tests were repeated 5 years after surgery. This may imply a functional involvement of the PAG/PVG in the neurodegenerative process. © 2013 Springer-Verlag Berlin Heidelberg.